A model for experimental infections with Vibrio (Listonella) anguillarum in first feeding turbot (Scophthalmus maximus L.) larvae under hatchery conditions - Planas, Miguel; Pérez-Lorenzo, María; Vázquez, José Antonio; Pintado, José (Aquaculture, 2005)
12 páginas, 4 figuras, 4 tablas Vibriosis is one of the main causes of mortality in all stages of fish. In larvae, further improvements on the control and knowledge of bacterial diseases require the development of models for experimental infections. A reproducible model for in vivo infections of first feeding turbot (Scophthalmus maximus) larvae with the pathogen Vibrio (Listonella) anguillarum is described. Experimental challenges were carried out under hatchery conditions considering different ways of delivery of V. (Listonella) anguillarum strain 90-11-287 serotype O1 to turbot larvae: via rotifers (orally) and via water of the larval rearing tanks (bath). The effect of the supernatant of the bacteria culture was also considered and discussed. The model proposed is based on the incorporation of the bacteria into previously enriched rotifers and the delivery to the larvae during the rotifer feeding period. The effect of infections was already evident 24–72 h after the first challenged day. Final mortalities (days 8–14) in infected larvae were 56–72% with respect to unchallenged larvae. Mortalities achieved by applying the protocol of infection are reliable, reproducible and adequate for experimental purposes. The model of infection via rotifers proposed in this study is a useful tool for experimental purposes in the larval rearing of marine fish. This work was supported by funds of the European Commission (Project PROBE, Contract No. Q5RS-2000-31457). Dr. J.A. Va´zquez had a postdoctoral contract (CSIC-I3P-PC 2003) financed by the European Social Fund. Peer reviewed